Bond between Steel Reinforcement Bars and Seawater Concrete - Adnan, Adnan; Parung, Herman; Tjaronge, M. W.; Djamaluddin, Rudy (Civil Engineering Journal, 2020)
In order to promote sustainable development in the remote islands this present research attempted to study the suitability of seawater, that available abundantly surrounding the remote islands with Portland composite cement (PCC) and crushed river stones to produce concrete. This research aims to utilize seawater, and Portland composite cement (PCC) to produce high-performance concrete in order to eliminate the main problems of clean water shortage in the low land areas and the remote islands. Infrastructure development can be sustained through the effective use of natural available local materials on the remote islands. The method used in this research is an experimental method in the laboratory. Two variations of concrete were made using freshwater and seawater, respectively as a mixing material with a water to cement ratio (w/c) of 0.55. The evaluation result on concrete compressive strength and bond strength of seawater concrete were discussed. Experimental results showed the compressive strength of the seawater concrete is lower by 6.26% as compared to the normal concrete at water-cement ratio (w/c) of 0.55. In addition, the bonding strength of steel bar embedded in seawater concrete is lower by 4.34% as compared to the bonding strength of steel bar embedded in normal concrete at water-cement ratio (w/c) of 0.55.Â Doi: 10.28991/cej-2020-SP(EMCE)-06 Full Text: PDF